2008
DOI: 10.1016/j.chroma.2008.01.062
|View full text |Cite
|
Sign up to set email alerts
|

High-speed gradient elution reversed-phase liquid chromatography of bases in buffered eluents

Abstract: We studied the run-to-run repeatability of the retention times of both non-ionizable and basic compounds chromatographed using buffered eluents. The effect of flow rate, organic modifier and other additives, buffer type/concentration, stationary phase type, batch-to-batch preparation of the initial eluent, gradient time, sample type and intra-day changes on retention repeatability were examined. We also assessed the effect of column storage solvent conditions on the inter-day repeatability. Although retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 52 publications
(39 reference statements)
1
21
0
1
Order By: Relevance
“…However, it was shown that only two column volumes (x = 2) can provide good runto-run repeatability in UHPLC conditions, even with charged compounds [23][24][25]. Starting from these values, the requirement in on-line LC x LC becomes:…”
Section: Peak Capacity In Lc X Lcmentioning
confidence: 97%
“…However, it was shown that only two column volumes (x = 2) can provide good runto-run repeatability in UHPLC conditions, even with charged compounds [23][24][25]. Starting from these values, the requirement in on-line LC x LC becomes:…”
Section: Peak Capacity In Lc X Lcmentioning
confidence: 97%
“…Additionally precise measurement of retention times allows the prediction of separations by using gradient elution training data through methods described by Snyder [19]. There have been a number of studies of the reproducibility of retention time in liquid chromatography that emphasize the importance of column equilibration [12, 20-32]. It is possible to achieve run to run gradient elution retention reproducibility to ± 0.002 min (standard deviation) in a bit more than two column volumes of re-equilibration (so-called “repeatable equilibrium”) [20].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies of the reproducibility of retention time in liquid chromatography that emphasize the importance of column equilibration [12, 20-32]. It is possible to achieve run to run gradient elution retention reproducibility to ± 0.002 min (standard deviation) in a bit more than two column volumes of re-equilibration (so-called “repeatable equilibrium”) [20]. Given a stable column and a good signal to noise ratio [8] the parameters that control retention time precision are: temperature ( T ), initial ( ϕ 0 ) and final ( ϕ f )mobile phase composition, gradient time ( t G ) and flow rate ( F ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations